Hubungan Dukungan Keluarga Dengan Kepatuhan Diet Terhadap Kualitas Hidup Pasien Diabetes Melitus Di Puskesmas Cikalong Kulon Tahun 2021: Relationship between Family Support and Diet Compliance with Quality of Life for Diabetes Mellitus Patients at Cikalong Kulon Health Center in 2021 - Oktavia, Silvi (Indonesian Scholar Journal of Nursing and Midwifery Science, 2022)
Introduction: Food regulation is the key to the management of Diabetes Mellitus, which at first glance looks easy but in reality, it is difficult to control your appetite. Quality of life is an individual's perception of his position in life, in the context of the culture, value system in which they are located, and their relationship to life goals, expectations, standards, and other related matters. Problems that cover the quality of life are very broad and complex including problems of physical health, psychological status, level of freedom, social relationships, and the environment in which they are located. This study was to determine the relationship of family support to dietary compliance with the quality of life of Diabetes Mellitus patients in the working area of ​​the Cikalong Kulon Public Health Center.  Methods: The research design used in this study was descriptive with a cross-sectional study approach, namely to determine Family Support and Dietary Compliance on the Quality of Life of Diabetes Mellitus Patients at the Cikalong Kulon Health Center.  Results: The population in this study were all DM patients in 2021 at the Cikalong Kulon Health Center, Cianjur Regency, amounting to 439 people. And the samples taken from this study were 82 respondents.  Discussion: Shows that supportive family support is 45 (31.7%) while those who are not supportive are 37 (26,1%), diet compliance shows that those who comply show 47 (33.1%) while those who do not comply show 35 (13.4%), while for good quality of life as many as 63 (44.4%) while those who are less good are 19 (13.4%). The researcher concludes that there is a relationship between Family Support and Diet Compliance on Quality of Life at the Cikalong Kulon Health Center in 2021 as indicated by the P-Value = 0.03 for Family Support and Diet Compliance and P-Value = 0.00 for Family Support and Life Compliance is 0.05, which means H0 is rejected and the sample supports or there is a significant relationship.